IMPROVING PROBLEM SOLVING ABILITY OF ELEMENTARY SCHOOL STUDENTS BY USING PROBLEM-BASED LEARNING MODELS - Faddylla Intan Maharani; Maria Montessori (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The background of this study is due to the low ability of problem-solving at elementary school students. The purpose of this study was to determine the improvement of the problem-solving abilities of elementary school students using problem-based learning models. This research was conducted in class IV SDN 07 KTK Solok City. This research was a classroom action research using Kemmis and Mc Taggart design. The results found that the initial ability of students to get an average score of 45.00, 68.00 for cycle 1 and 79.00 for cycle 2. The results of this study indicated an increase in the problem-solving ability of elementary school students by using problem-based learning models. The research implications can be used as a reference for developing the problem-solving abilities of elementary school students.